Proses Komunikasi Asosiasi Duta Wisata Indonesia (ADWINDO) Kota Padang Pada Program Goes To School di Kota Padang - Rani Rani; Dion Eriend (Pusat Penelitian Dan Pengabdian Masyarakat STIEPARI Semarang, 2024)
The city of Padang has a variety of tourist attractions in every corner, be it culinary, natural, cultural, religious, historical and other tourist riches. Padang City Tourism is a tourist area that is very popular. With the formation of the Padang City Tourism Ambassador Union Uda as an extension of the Tourism Department, it cannot be denied that this is known to the entire community and the public. Data collection techniques are carried out through observation, interviews and documentation. This research uses descriptive qualitative methods. In this research, it can be seen how the communication process carried out by Uda Uni Duta Wisata in the Goes To School work program is carried out to promote tourism and preserve customs and culture in the city of Padang, developing information that is packaged through socialization or through social media. the effectiveness of using Uda Uni as a tourist ambassador for the city of Padang as a tourism, customs and culture role model who is able to become an extension of the government, to assist the government in increasing public knowledge about tourism and increasing tourist visits to the city of Padang. By sending uda uni as one of the tourism drivers, it can make it easier for the public to reach information through work programs carried out by uda uni Padang city, both physically through outreach and through the media. From this research, it can be seen how communication from Uda Uni Padang City Tourism Ambassadors socializes so that the public can receive information well.